PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN ISPRING SUITE 11 UNTUK MELATIH KEMAMPUAN REPRESENTASI MATEMATIS PADA MATERI OPERASI BILANGAN PECAHAN - Gustiana, Irpan; Nugraha, Depi Ardian; Santika, Satya (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2024)
This research aims to test the feasibility of assisted learning media ISpring suite 11 on fractional number operations material to practice skills mathematical representation. The research method uses Research Development (RD) with the ADDIE model. Data collection techniques are carried out by interviews, distribution of questionnaires and mathematical representation ability test questions. Instruments that used are interview grid sheets, questionnaires for assessing feasibility and student responses as well as ability test questions to assess effectiveness of use instructional Media. The data sources for this research are two media experts and two experts material to assess in terms of technical quality, as well as the quality of the content and objectives and participants class VII students of SMP Negeri 5 Tasikmalaya to find out students' responses as well effectiveness of the use of learning media. The results of this research are in the form of media applications learning that can be used on Android smartphones with the name HiFraction. The feasibility of this learning media is assessed based on validity assessments, practicality and effectiveness. This learning media is declared very suitable by experts media and material experts as well as students responded very well to use of this learning media